Mean Pain Score Before and After Wrist Splinting for Carpal Tunnel Syndrome Presenting to Orthopedic Department Hayatabad Medical Complex, Peshawar - Sayed Sajjad Ali, Afaq Uddin, Muhammad Shahab, Faizan Ali Janjua, Saman Zia, Irfan Ahmad, Ayaz Uddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Median nerve neuropathy, often known as carpal tunnel syndrome (CTS), is a pathological condition that develops when the median nerve becomes entrapped within the carpal tunnel, resulting in pain, numbness, and tingling sensations. The most popular non-surgical procedure right now is splinting the wrist with a rigid splint, mainly at night and occasionally in conjunction with other therapies. Objective: To determine mean change in pain score before and after wrist splinting for carpal tunnel syndrome presenting to orthopedic department Hayatabad Medical Complex, Peshawar. Methods: This Quasi Experimental Study (Uncontrolled Trial) was held in the Orthopedic Department Hayatabad Medical Complex Peshawar for six months duration from 5th September 2020 to 6th March 2021 after approval of synopsis. A total of 60 patients with CTS were included in the study in a consecutive manner and subjected to wrist splinting. Baseline and follow up pain scores were measured at 6th post splinting week. Results: The mean age of the sample was 42.3 + 12.8 years. While distributing the patients with regards to gender, we observed that in our study 65% of the sample was male and 35% were female gender. The mean BMI was 25.2 + 3.4kg/m2 and 13.3% of sample was diabetic. Mean use of splint / day was 5.3 + 2.2 hours and 43.3% used ibuprofen as analgesic. Mean baseline pain score of the sample was 8.9 + 0.9 and mean follow up pain score at 6th week of splint use was 4.2 + 1.5 (p < 0.001). Conclusion: Wrist splinting is an effective conservative treatment for CTS in terms of significant pain relief after 6 weeks and is not dependent upon BMI, gender, diabetes or type of NSAIDs used. However, our study sample size was too small to draw conclusions there is no evidence of functional improvement after splinting. We recommend more studies (interventional) on large sample size and taking into account pain as well as functional assessment to develop future guidelines for the treatment of CTS using wrist splinting Keywords: Carpal tunnel syndrome, Splinting, diabetes, Body mass index, Pain, Visual analogue scale.